Video Interaktif Bagi Ibu Nifas Primigravida Sebagai Edukasi Peningkatan Motivasi Pemberian ASI Ekslusif - Sumarni, Sumarni; Karlina, Ninik (Madu : Jurnal Kesehatan, 2024)
The quality and quantity of information are factors that influence the level of motivation of mothers in exclusive breastfeeding, therefore interactive video-based education is carried out as a means of delivering quality information and is expected to increase the motivation of mothers in providing exclusive breastfeeding. To determine the effect of interactive video-based education on increasing motivation for exclusive breastfeeding in primigravida postpartum mothers. Pre-experimental Design Method. The population in this study amounted to 50 people and the sample used was 44 primigravida postpartum mothers at RSIA Ananda Makassar City. The research instrument was a questionnaire sheet. Respondents were given interactive video-based education on the first day of the postpartum period then given video marching education a week later, then given on day 14 of the postpartum period. Univariate and bivariate analysis using the Wilcoxon statistical test. the results of the study with the Wilcoxon test obtained a value of ρ = 0.000 < α = 0.05, so that from these results there is an effect of interactive video-based education on increasing motivation for exclusive breastfeeding in primigravida postpartum mothers. the provision of interactive video-based education can be a means of obtaining quality information to increase the motivation of postpartum mothers in providing exclusive breastfeeding for their babies.